A numerical investigation of the plenum chamber aerodynamic behaviour of mechanical draught air-cooled heat exchangers - Meyer, C. J. (Christiaan Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.)--University of Stellenbosch, 2000.